Honesty and Intermediation: Corporate Cheating, Auditor Involvement and the Implications for Takeoff - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2006)
We examine self-enforcing honesty in firm-investor relations in an imperfect public information game. Minimum firm size requirements and moral hazard limit ability to raise outside capital, yielding a floor on personal wealth required to enter entrepreneurship. Credible auditing could create efficiency gains. We propose mandatory disclosure of audit fees and an interpretation of international differences in shareholding patterns. We endogenize auditor-firm collusion and extortion by auditors. We embed our game-theoretic analysis in a general equilibrium model to generate unique equilibria that trace the impact of the distribution of wealth on the existence of the market and consequences for development.